2010
DOI: 10.1586/erv.09.161
|View full text |Cite
|
Sign up to set email alerts
|

BCG vaccination and leprosy protection: review of current evidence and status of BCG in leprosy control

Abstract: The bacillus Calmette-Guérin (BCG) vaccine, initially developed to provide protection against TB, also protects against leprosy; and the magnitude of this effect varies. Previous meta-analyses did not provide a summary estimate of the efficacy due to the heterogeneity of the results. We conducted a meta-analysis of published data including recently published studies (up to June 2009) to determine the efficacy of BCG protection on leprosy and to investigate whether age at vaccination, clinical form, number of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(119 citation statements)
references
References 29 publications
4
111
0
4
Order By: Relevance
“…Several studies have shown that the BCG vaccine protects against leprosy, being one of the priority interventions established by the World Health Organization (WHO) to control the disease 50 . Conversely, some studies have suggested varied protection by the BCG vaccine and this may be related to genetic factors 68,69 ., In this study most patients with leprosy who had a BCG vaccination scar and a Th1 immune response were tuberculoid while most patients without a BCG scar and with a Th2 response were lepromatous. Some studies demonstrate that BCG vaccination makes the individual most likely to develop a profile of M1 macrophages, inducing them to produce pro-inflammatory cytokines such as IL-1 and TNF-α, thereby developing a greater resistance to the bacteria 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the BCG vaccine protects against leprosy, being one of the priority interventions established by the World Health Organization (WHO) to control the disease 50 . Conversely, some studies have suggested varied protection by the BCG vaccine and this may be related to genetic factors 68,69 ., In this study most patients with leprosy who had a BCG vaccination scar and a Th1 immune response were tuberculoid while most patients without a BCG scar and with a Th2 response were lepromatous. Some studies demonstrate that BCG vaccination makes the individual most likely to develop a profile of M1 macrophages, inducing them to produce pro-inflammatory cytokines such as IL-1 and TNF-α, thereby developing a greater resistance to the bacteria 70 .…”
Section: Discussionmentioning
confidence: 99%
“…Leprosy is the leading infectious cause of disability (Rodrigues & Lockwood 2011). Although the prevalence of leprosy has declined substantially over the past 50 years (Merle et al 2010), transmission of the disease continues and it remains a relevant public health problem worldwide (WHO 2008).…”
mentioning
confidence: 99%
“…It is noteworthy, however, that leprosy remains prevalent in countries with widespread BCG vaccination programs and, as is the case for TB, protection afforded by BCG vaccination against leprosy appears to wane over time. Regardless, systematic meta-analyses indicate that BCG vaccination has a protective efficacy of approximately 50% (Setia et al 2006, Merle et al 2010). In addition, protection appears to be better against the MB than PB forms.…”
Section: Resultsmentioning
confidence: 99%